Pengaruh Bobot Umbi G1 Terhadap Pertumbuhan Dan Hasil Tanaman Kentang (Solanum tuberosum L.) Varietas Granola Generasi Dua (G2): Program Studi Agroteknologi Fakuktas Pertanian Universitas Andalas - Marshanda, Marshanda; Suliansyah, Irfan; Swasti, Etti (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2024)
Potato (Solanum tuberosum L.) is one of the horticultural commodities that become alternative foods as a source of carbohydrates other than wheat, rice, and corn. One of the efforts to increase potato production can be done through the selection of quality seeds. The selection of G1 generation potato seeds is used because it has not undergone deteoration so that the quality of the seeds is still maintained. This study aims to determine the effect of G1 tuber weight on the growth and yield of potato (Solanum tuberosum L.) G2 Granola varieties. This research was conducted at the Green House of the Pusat Alih Teknologi dan Pengembangan Kawasan Pertanian (PATPKP) of Andalas University located in Jorong Galagah, Nagari Alahan Panjang, Lembah Gumanti District, Solok Regency from August to November 2023. This study used a Completely Randomized Design (CRD) consisting of 4 levels of treatment, namely the weight of G1 tubers (5-15, 16-30, 31-45, and 46-60) with 3 replications, where there were 12 experimental units. The data obtained were statistically analyzed with the F test at a real level of 5% and if the effect was real, it was continued with Duncan's New Multiple Range Test (DNMRT) with a level of 5%. The results showed that there was an influence of the weight of G1 tubers on the growth and yield of potato plants of the G2 Granola variety. G1 tuber weights of 46-60 g give the best results in increasing plant height growth, number of shoots, stem diameter, and fresh weight of tubers per plant.